MANAJEMEN DISTRIBUSI PRODUK KOPRA PADA KELOMPOK UMKM DESA LAPEO DI KECAMATAN CAMPALAGIAN KABUPATEN POLEWALI MANDAR - Fauzan, Muhammad; Irawati, Irawati (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2023)
Kelompok UMKM Desa Lapeo has quite abundant produce, one of which is copra products. Through this community service training, it aims to provide distribution management training on copra products to provide knowledge that can be applied to the business run by Kelompok UMKM Desa Lapeo. Kelompok UMKM Desa Lapeo faces several problems, especially in determining product distribution, the first problem faced is the lack of knowledge in managing product distribution. The second problem is the competition between copra products and surrounding areas that have similar plantation products with Kelompok UMKM Desa Laepo. The third problem is the difficulty in managing inefficient product storage which can affect the quality of copra products. The solution offered is to increase understanding of distribution management in Kelompok UMKM Desa Lapeo, then maximize the determination of the right product distribution to improve the economy of owner business.